1997
DOI: 10.1074/jbc.272.13.8198
|View full text |Cite
|
Sign up to set email alerts
|

The Abd-B-like Hox Homeodomain Proteins Can Be Subdivided by the Ability to Form Complexes with Pbx1a on a Novel DNA Target

Abstract: Previous studies showed that the Hox homeodomain proteins from paralog groups 1-8 display cooperative DNA binding with the non-Hox homeodomain protein Pbx, mediated by a canonical YPWM. Although the Abd-B-like Hox proteins in paralogs 9 -13 lack this sequence, Hoxb-9 and Hoxa-10 were reported to bind with Pbx1a to DNA. We show that these interactions require a tryptophan 6 amino acids N-terminal to the homeodomain. Binding site selection for Hoxb-9 with Pbx1a yielded ATGATTTACGAC, containing a novel TTAC Hox-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
133
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 37 publications
9
133
1
Order By: Relevance
“…38 PBX1a is involved in translocations in human ALL and is a known binding partner for many HOX genes including those studied here. 13 Interestingly, the pattern of PBX1a expression in subpopulations of normal cells was similar to that for the four HOX genes and MEIS1. However, its expression was difficult to detect in AML blasts.…”
Section: Figurementioning
confidence: 82%
See 1 more Smart Citation
“…38 PBX1a is involved in translocations in human ALL and is a known binding partner for many HOX genes including those studied here. 13 Interestingly, the pattern of PBX1a expression in subpopulations of normal cells was similar to that for the four HOX genes and MEIS1. However, its expression was difficult to detect in AML blasts.…”
Section: Figurementioning
confidence: 82%
“…10 Transcripts for HOXA9, A10, B3 and B4 are detected in malignant cells from various subtypes of AML, but interestingly, expression of at least one of these (A10) is not seen in acute promyelocytic leukemia. 11,12 PBX1a, a DNA binding partner of several HOX gene family members, 13 is fused to E2A in acute lymphoblastic leukemia (ALL) containing the t(1;19). 14 Another HOX binding partner, Meis1, 15 is activated by retroviral insertion together with Hoxa7 and Hoxa9 in myeloid leukemia in BXH-2 mice.…”
Section: Introductionmentioning
confidence: 99%
“…Competition for binding sites has in the past seemed unlikely because of varying binding-site preference among anterior and posterior Hox proteins. Anterior Hox proteins prefer a G at the second position of the 5Ј-TNAT/CNNN-3Ј half-site, middle Hox proteins accept a G or A, whereas the more posterior proteins bind G, A, or T. A preference for C in the fourth position is exhibited by the most posterior Hox proteins (Shen et al 1997). Given that Hox proteins contain the same four helix-3 residues that make direct DNA base contacts in the major groove, this specificity has been postulated to be determined by residues in the N-terminal arm through interactions with the minor groove of DNA (Ekker et al 1994) and modulated by the interaction with PBC proteins Passner et al 1999;Piper et al 1999).…”
mentioning
confidence: 96%
“…The PBC family, which includes human Pbx1 and Drosophila Exd, belongs to a class of proteins that contains the TALE (three-aminoacid loop extension)-type homeodomain, so named because of a three-amino-acid insertion between homeodomain residues 23 and 24 in the loop between helices 1 and 2 (Mann 1995;Mann and Chan 1996;Bü rglin 1997). A subset of vertebrate Hox proteins interacts with Pbx1 via a conserved six-amino-acid motif, or hexapeptide, enabling cooperative DNA binding (Chang et al 1995;Neuteboom et al 1995;Peltenburg and Murre 1996;Shen et al 1996Shen et al , 1997Passner et al 1999;Piper et al 1999).…”
mentioning
confidence: 99%
“…A number of studies have demonstrated that Pbx and exd proteins increase the in vitro DNA binding affinities of many Hox and several non-Hox homeodomain proteins (6-8, 16, 20, 28, 37, 39, 41, 43, 49, 50, 53). Pbx-Hox cooperative DNA binding occurs through adjacent DNA half sites and requires highly conserved motifs flanking the Hox and Pbx homeodomains (7,20,25,37,43,50). Interactions with Pbx also result in enhanced DNA binding specificities by Hox proteins due to modulation of the Hox homeodomain N-terminal arm, which contacts nucleotides in the DNA minor groove (8, 26).…”
mentioning
confidence: 99%